Effect of pesticide exposure on acetylcholinesterase activity in subsistence farmers from Campeche, Mexico - Rendón von Osten, Jaime
The authors surveyed agricultural production methods and pesticide use among subsistence farmers (campesinos) in 4 rural communities of Campeche, Mexico. Self-reports of symptoms of poisoning resulting from occupational pesticide exposure were elicited by questionnaire (N = 121), and acetylcholinesterase (AChE) activity during insecticide use was evaluated from blood samples (N = 127). In individuals from 2 of the 4 communities, AChE activity was significantly lower (p < 0.05) than the mean of activity determined for individuals in a reference group. Results of this study show that erythrocyte AChE inhibition provides a good biomarker of exposure to organophosphate pesticides in field studies with human populations. Carbamates, particularly carbofuran, seem to be more associated with exuberant and diversified symptomatology of pesticide exposure than organophosphates. Studies in field communities where both carbamates and organophosphates are suspected to exist should include blood AChE determinations, symptomatology surveys, and socioeconomic questionnaires. The authors recommend that the Mexican National Health Ministry authorities specify additional provisions regarding the use of protective equipment and the adoption of other safety practices during field work, increase information campaigns about the risks of pesticide use and the value of safety practices, and increase programs of medical monitoring and assistance for rural communities dealing with pesticides.